«No one else can make you change». Formazione, giovinezza, musica, a partire dal Sessantotto - Elena Madrussan (Firenze University Press, 2019)
Beyond the number of stereotypes concerning 1968, in that year the intersection between youth and music achieved a full-fledged Bildungsroman that recovered the poetry of disquiet as powerful tool for relief and self-affirmation, for modelling/transfer and self-knowledge, for imaginative search and existential project. After 1968, through chords and lyrics, the music styles and the identity differences are evolved as real strategies of dissent. Behind major discursivity, in fact, a rich relationship was built between music and the making of divergent personality, of the project of possibility and of the action against conformism, that ended up with making music the complex and very effective semantic field for an implied education so far rather underestimated by pedagogical culture.